Recent Development in the Topologies for Photovoltaic Module Integrated Converters - Li, Q.; Wolfs, Peter (IEEE, 2006)
The annual world PV cell/module production is growing at almost an exponential rate and has reached 1727 MW in 2005. Building integrated PV (BIPV) projects are emerging as the strongest part of the PV market and grid interactive inverters are a key component in determining the total system cost. Module integrated converter (MIC) technology is one approach that may assist in driving down the balance of system costs to secure an improved total system cost. This paper concentrates on the topology study of the photovoltaic MICs in the power range below 500 W and covers most topologies recently proposed for MIC applications. The MIC topologies are classified into three different arrangements based on the dc link configurations. A systematic discussion is also provided at the end of the paper that focuses on the major advantages and disadvantages of each MIC arrangement. These are considered in detail and will provide a useful framework and point of reference for the next generation MIC designs and applications